DAMPAK E-BILLING, E-FILING, DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Terhadap Wajib Pajak Orang Pribadi yang Terdaftar di Kantor Pelayanan Pajak Pratama Semarang Candisari) - Ronald Wahono, 15.05.52.0146; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2019)
Tax is one of the income to support the life of the country. This study aims to examine and analyze the effect of the application of e-Billing, e-Filing, and understanding of taxation on tax compliance. The population in this study were individual taxpayers at KPP Pratama Semarang Candisari. The research method used is a quantitative method with a questionnaire as a basis for collecting data. The sampling method is done by purposive sampling method, with the criteria of individual taxpayers employees who have two or more different sources of income and individual taxpayers who are non-employees who have applied e-Billing and e-Filing. The number of respondents used was 105 respondents. The analytical tool used is multiple linear regression. The results showed that the application of e-Billing had no significant effect on taxpayer compliance, the application of e-Filing had no significant effect on taxpayer compliance, and understanding taxation had a significant positive effect on taxpayer compliance.